PENGEMBANGAN LKPD MODEL INKUIRI TERBIMBING YANG MENGAKOMODASI KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Hasanah, Nenden Nidaul; Dinny Mardiana; Nurjanah (Uninus Journal of Mathematics Education and Science (UJMES), 2024)
The research backgoround is low critical thinking skills and motivation student learning, and the unvaibility of accomodating LKPD students critical thingking skills. The aim of this research is develop LKPD based on Guided Inquiry that is valid, practical, facilitating the ability to motivate intelligent thinking, as well as students learning on subject of flat side shapes (cubes and blocks) at junior high school level. Qualitative research approach, development research method with ADDIE research design. The research location is SMP Negeri 2 Kertasari implementation in the 2022/2023 academic year. The research subject are students class VIII and math teacher. Instrument used are documents, personal guidelines, validation sheets, and anwer sheets. The results of the research show that the LKPD has been develop is valid.